Investing in the informal sector in Ibadan entrepreneurship factors and women participation (2021)
Most of the literature on female entrepreneurs in developing economies has concentrated on one or two of these entrepreneurial factors. This study, therefore, addresses this gap by using a qualitative approach to explore the factors that influence women's participation in Nigeria s informal sector as a whole. It begins with a review of related definitions in the literature as a source of questions and definitions that can be applied to the informal sector. Women entrepreneurs were chosen using a stratified sampling technique based on areas with specific features within each market (small, community and large). Eight separate sectors of activity (market traders, food vendors, firewood and charcoal makers, accessories and decorations, garments dealers (readymade), beauty salons, fashion design and production) were sampled in each of these markets, demonstrating the dominance of different informal sectors. Data were collected from 21 Nigerian female entrepreneurs using qualitative interviews in Ibadan. Participants consent were sought before the interview took place. The transcribed data was analysed using a thematic approach. The findings of the interview revealed that vision, goal- oriented mindset, risk-taking, decision-making, money management, optimism, network ability, and innovation all contributed to women’s informal sector entrepreneurial activity. As a result, the researcher recommends that potential entrepreneurs in the informal sector require these factors to succeed